Factors influencing green purchase intention among Malaysian consumers / Liyana Adibah Tahir - Tahir, Liyana Adibah (Faculty of Business and Management, 2020)
This research was conducted to carry out a study entitled “Factors Influencing Green Purchase Intention among Malaysian Consumers”. The purpose of this study is to investigate the relationship between four independent variables with dependent variable to identify which factor is most important towards purchase intention towards green products. Basically, it consists of four factors influencing on Malaysian consumer focusing in Bandar Melaka and the factors are green packaging, green product value, eco-label, green advertisement. In order to complete this study, few hypotheses were constructed and 150 respondents were chosen as respondent. The data was obtained from primary data by using questionnaire. All data collected through the questionnaire were analysed systematically by Statically Package for Social Science (SPSS). Form the correlation testing, the result shows four independent has relationship with dependent variable. In terms of hypothesis result, all are accepted. For multiple regression analysis, the most influential factor is green packaging.